Gender and entrepreneurship research: A review of methodological approaches*. (May 2016) - Henry, Colette; Foss, Lene; Ahl, Helene
This article presents the findings of a systematic literature review (SLR) of the gender and entrepreneurship literature published in 18 journals over a 30-year period. The SLR sought to identify methodological trends in the field of gender and entrepreneurship and to critically explore the type of methodological innovations needed in future scholarship. Findings reveal a proliferation of large-scale empirical studies focused on male/female comparisons, often with little detail provided on industry sector or sampling methods and with either a weak, or no feminist critique whatsoever. We argue that future scholars must develop the methodological repertoire to engage with post-structural feminist approaches; this may require a radical move towards more innovative, in-depth qualitative methodologies such as life histories, case studies or discourse analysis.